Nanoscale Magnetic Materials and Applications 2009
DOI: 10.1007/978-0-387-85600-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and Magnetism in Silicon and Germanium Clathrates

Abstract: Clathrates are materials containing closed polyhedral cages stacked to form crystalline frameworks. With Si, Ge, and Sn atoms populating these frameworks, a wide variety of electronic and vibrational properties can be produced in these materials, by substitution upon framework sites or through incorporation of ions in cage-center positions. Commonly-formed structures include the type I, type II, and chiral clathrate types, whose properties will be described here. Ba 8 Si 46 with the type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 90 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…The synthesis involved melting the pure-elements, followed by annealing and hot pressing. Powder X-ray diffraction (XRD) and analysis provided full structural details of the samples, and dispersive X-ray spectroscopy was measured to determine the compositions of the samples (nominal x = 0, 3,6,10,13,18,25,35,41) ) and thereby lead to reduced carrier concentration. The previous results also showed that, while the lattice constants of the compounds decease linearly with increasing Si content, some internal parameters such as the Si occupation at the 24k site show nonlinear behavior.…”
Section: Synthesis and Sample Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis involved melting the pure-elements, followed by annealing and hot pressing. Powder X-ray diffraction (XRD) and analysis provided full structural details of the samples, and dispersive X-ray spectroscopy was measured to determine the compositions of the samples (nominal x = 0, 3,6,10,13,18,25,35,41) ) and thereby lead to reduced carrier concentration. The previous results also showed that, while the lattice constants of the compounds decease linearly with increasing Si content, some internal parameters such as the Si occupation at the 24k site show nonlinear behavior.…”
Section: Synthesis and Sample Characterizationmentioning
confidence: 99%
“…6,[8][9][10][11] There have been many efforts to study Ba 8 Ga 16 Ge 30 and similar ternary semiconducting clathrates since they can have large thermoelectric figures of merit, [3][4][5] ZT E 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many research groups are engaged in the research and development of this superconducting material. Any substitutions of Si on the framework or Ba in the center of the cage can profoundly affect superconductivity [11][12]. The destructive effect on superconductivity generally comes from several reasons: (i) the decrease in density of state at Fermi-level (N(E F )), (ii) a lowering of the carrier concentration, (iii) a breakage of the integrity of the sp 3 -hybridized network, (iv) the magnetic breakdown of paired electrons, and (v) the red shift of phonon dispersion spectra, which resulting in the depression of electron-phonon coupling.…”
Section: Introductionmentioning
confidence: 99%